Methodological framework - Warmuth, Julia-Rita; Weiß, Julia; Pauknerová, Daniela; Hanzlík, Jan; Tosun, Jale; Kittel, Bernhard (Intergenerational transmission and economic self-sufficiency, 2023)
This chapter provides details on our methodological approach, including the types of interviews conducted, our interviewee sampling strategy, the way we conducted the interviews, and the analysis of the interview data. Since we adopt a qualitative approach, the analytical framework consists of general guidelines, which helps to attain our common research interest as well as to grant flexibility to the individual research teams so that they can concentrate on specific features of their respective cases.